Numerical study of circle hollow section (CHS) Y-joints in fire (ST-25AB) - Deng, Yue (2013)
In this research, the structural behaviour of circular hollow section Y-joints in fire condition had been studied. The objectives of this research are mainly three which are: (1) to study the behaviour of circular hollow section (CHS) Y- joints subjected to in-plane bending. (2) to build a database of the ultimate strengths of CHS Y-joints at different temperatures (3) to compare Y-joint behaviour and strength with the previous study on T-joints.